The Effect of Abdominal Massage and Fecal Elimination Exercises in Treating Constipation in Stroke Patients: Case Report - Alfina Damayanti Kurnia; Erik Kusuma; Evy Aristawati (Health and Technology Journal (HTechJ), 2024)
Impaired physical mobility in stroke sufferers can cause constipation, which will cause effects such as hemorrhoids, rectal prolapse, and even increased intracranial pressure. Abdominal Massage and exercises elimination of feces elimination exercises are non-pharmacological strategies that can overcome this problem of constipation. The study aimed to determine the effect of abdominal massage therapy and exercise in the elimination of feces in overcoming constipation, which is characterized by controlling fecal output, bowel complaints, fecal consistency improved, bowel movement frequency improved, and intestinal peristalsis improved. The method used is a case study, a sample in a case study. This is a stroke patient who is constipated. Data collection uses techniques, interviews, and observations. The Constipation Analysis Scale instrument was used to assess the degree of constipation. Abdominal massage therapy and fecal elimination exercises are given once a day when you wake up for 30 minutes. The research results showed that respondents have no complaints about defecation, the stool consistency is soft, and there is increased intestinal peristalsis after being given intervention. Abdominal massage therapy and fecal elimination exercises can overcome this constipation in stroke sufferers. This intervention can be used as a possible non-pharmacological action that can be applied as a treatment to treat constipation and facilitate bowel movements instead of using laxatives. This intervention is educational and can be done anywhere without requiring medical assistance.